1980
DOI: 10.2340/00015555924447
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Features of Atopic Dermatitis

Abstract: is missing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
199
0
7

Year Published

1989
1989
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,910 publications
(267 citation statements)
references
References 0 publications
4
199
0
7
Order By: Relevance
“…Even though some controversies still remain over the plausible mechanisms and epidemiology of comorbid atopic disease in AD, 10 the presence of comorbidities like asthma, hay fever and food allergy are part of the diagnosis criteria for AD. 11 , 12 In a previous small Argentinean study with severe AD, prevalence of rhinitis and asthma were reported as higher; 13 however, our study included a larger sample with pediatric and adult patients, probably representing closely the real-world along the whole severity spectrum of AD patients population in the country.…”
Section: Discussionmentioning
confidence: 84%
“…Even though some controversies still remain over the plausible mechanisms and epidemiology of comorbid atopic disease in AD, 10 the presence of comorbidities like asthma, hay fever and food allergy are part of the diagnosis criteria for AD. 11 , 12 In a previous small Argentinean study with severe AD, prevalence of rhinitis and asthma were reported as higher; 13 however, our study included a larger sample with pediatric and adult patients, probably representing closely the real-world along the whole severity spectrum of AD patients population in the country.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, 11 healthy individuals with negative patch test results were assigned to the control group (Table 1; non‐ACD group; n = 11; 3 males, 8 females; mean age = 41.18 ± 10.28 years old, range = 24–53 years old). No ACD or control group subject had a history of previous atopic dermatitis, according to the diagnostic criteria of Hanifin and Rajka 12 . Four cryopreserved skin samples, obtained from patients with severe atopic dermatitis (AD group; mean age = 28.5 ± 3.11; age range = 25–32 years old; mean EASI = 48.88 ± 8,82, EASI range = 38–57), were also selected as a control group with dermatitis.…”
Section: Methodsmentioning
confidence: 99%
“…Seventy patients with AD were enrolled in the study. The diagnosis of AD was made according to the HanifinRajka criteria [8]. The age, gender, and history of personal or family history of allergic rhinitis or asthma were taken from the patients or their caregivers.…”
Section: Methodsmentioning
confidence: 99%
“…There are major and minor criteria for the diagnosis of AD that are established by Hanifin and Rajka [8]. The major criteria (must have 3 or more) include pruritus, typical mor-phology and distribution (flexural lichenification in adults, and facial and extensor involvement in infancy), Dermatitis (chronically or chronically relapsing), and Personal or family history of atopy-asthma, allergic rhinitis, and AD.…”
Section: Introductionmentioning
confidence: 99%